Сelebrating Scientific Acheivements of Scientists - Milestone Celebrators and Scientific Potential of the Ukrainian Studies - Kononenko, Vitaly (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
There exists an ongoing tradition to celebrate milestone birthdays and other important anniversaries of famous scientists, who have devoted decades of their lives to fruitful scientific work. The tradition is an old one and can be traced back to the medieval Europe. Primarily, a celebration like that is held not only to glorify the birthday person as a scientist, but also to summarize their work in a particular field of scientific knowledge; it is an event open for discussions and exchange of views. Events of this kind provide young researchers with an opportunity to prove themselves to famous men of science, whose students and followers they are. We can mention the anniversary events organized to celebrate achievement of some of the prominent figures of the Ukrainian science. The list includes Mykhailo Hrushevsky, Volodymyr Vernadsky, Danylo Zabolotny, Yuriy Kondratiuk, Yevhen Paton, and other renowned personalities, whose anniversaries and milestones have been accompanied by scientific conferences, symposiums, monographs and other scientific publications.